World poverty: global inequality and the modern world system - Kerbo, Harold R. (Boston: McGraw-Hill, 2006)
(NtOW^ HURAANGUJs
Includes bibliographical references (p. [267-285])and index.
Keywords: Poverty; Poverty -- Case studies